Research on the impact of health empowerment on self-management in older patients with chronic disease: based on chain mediating effect analysis - Wang, Tiemei; Huang, Shiqing; Liu, Jinxia; Liu, Yan (Frontiers in Public Health, 2025)
ObjectiveThis study investigates the mediating effect of chronic disease resource utilization and self-efficacy on the relationship between health empowerment and self-management in older adults with chronic diseases.MethodsA convenience sampling method was used to select 826 older adult patients with chronic diseases from 12 tertiary hospitals in Sichuan Province. General demographic information was collected using a questionnaire, and self-management, health empowerment, chronic disease resource utilization, and self-efficacy were assessed using standardized scales. Data were analyzed using SPSS 25.0, and the PROCESS macro was employed to test the mediating effect of chronic disease resource utilization and self-efficacy.ResultsThe mean score for self-management was 40.89 ± 11.71, for health empowerment was 22.07 ± 7.13, for chronic disease resource utilization was 67.02 ± 10.65, and for self-efficacy was 21.25 ± 4.77. Health empowerment was positively correlated with chronic disease resource utilization (r = 0.87, p < 0.001) and self-efficacy (r = 0.75, p < 0.001), as well as self-management (r = 0.73, p < 0.001). Chronic disease resource utilization was positively correlated with self-efficacy (r = 0.68, p < 0.001), and self-management (r = 0.86, p < 0.001). Self-efficacy was positively correlated with self-management (r = 0.68, p < 0.001). Health empowerment can directly and positively affect self-management, with an estimated value of 0.174, accounting for 37.6% of the total effect, and it can influence self-management through chronic disease resource utilization, with an estimated value of 0.123, accounting for 26.6% of the total effect. Health empowerment can influence self-management through self-efficacy, with an estimated value of 0.103, accounting for 22.2% of the total effect, and it can also influence self-management through the chain mediating effect of chronic disease resource utilization and self-efficacy, with an estimated value of 0.063, accounting for 13.6% of the total effect.ConclusionHealth empowerment can directly affect the self-management of older adults patients with chronic diseases, and it can also influence it indirectly through the utilization of chronic disease resources and self-efficacy. The utilization of chronic disease resources and self-efficacy play a mediating role between health empowerment and self-management. Healthcare providers can improve health empowerment and self-management in older adult patients through effective interventions to enhance chronic disease resource utilization and self-efficacy.